Complementary and alternative medicine for the treatment of multiple sclerosis - Yadav, Vijayshree (2010)
Multiple sclerosis (MS) is a chronic disabling disease of the CNS that affects people during early adulthood. Despite several US FDA-approved medications, the treatment options in MS are limited. Many people with MS explore complementary and alternative medicine (CAM) treatments to help control their MS and treat their symptoms. Surveys suggest that up to 70% of people with MS have tried one or more CAM treatment for their MS. People with MS using CAM generally report deriving some benefit from the therapies. The CAM therapies most frequently used include diet, omega-3 fatty acids and antioxidants. There is very limited research evaluating the safety and effectiveness of CAM in MS. The most promising among CAM therapies that warrant further investigation are a low-fat diet, omega-3 fatty acids, lipoic acid and vitamin D supplementation as potential anti-inflammatory and neuroprotective agents in both relapsing and progressive forms of MS. There is very limited research evaluating the safety and effectiveness of CAM in MS. However, in recent years, the NIH and the National MS Society have been actively supporting the research in this very important area.